PENGARUH LATIHAN SLED TOWING OR SPEED CORD TOWING TERHADAP KECEPATAN LARI PEMAIN SEPAKBOLA KEPELATIHAN OLAHRAGA ANGKATAN 2013 UNIVERSITAS RIAU - Miki Donal; Slamet '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study originated from the observation research conducted on campus pendor that many football players Forces Sports Coaching Education In 2013 the University of Riau who lack running speed during the attack and survived when so often defeat in the sprint steal the ball collided with an opposing player. The goal in this study to see Influence of Exercise Sled Towing Towing Or Cord Speed to Speed Coaching Sport Student Football Players Forces 2013 University of Riau. In this study, researchers took a student population of coaching soccer team Sport Force 2013, which amounted to 21 people. The sample in this study using total sampling technique, where all the population sampled. The data obtained from the test speed of 40 yards. Data was analyzed using t-test. Based on research conducted on 21 samples by performing preetes (initial test) run 40 yards. Then proceed with treatment (Sled Towing Towing Or Cord Speed) during 16 sessions, once that is done postes (run 40 yards), the results obtained from the pretest and posttest analyzed by t-test. Hypothesis testing results show that the results tcount of 7.364 to 1.725 ttabel then H_0 rejected, H_a accepted, on the level of alpha (á) 0.05. It can be concluded that there are significant Sled exercise Towing Or Cord Speed Towing against running speed sports coaching football players Forces 2013 University of Riau.Keywords: Sled Towing Towing Or Cord Speed, Speed